Hippocampal Sulcus Remnant: Common Finding in Nonelderly Adults on Ultra-High-Resolution 7T Magnetic Resonance Imaging. Issue 1 (January 2020) - Yamashita, Koji; Zong, Xiaopeng; Hung, Sheng-Che; Lin, Weili; Castillo, Mauricio
Abstract : Objective: The objective of this study was to investigate the frequency of hippocampal sulcus remnants (HSRs) in nonelderly adults using ultra-high-resolution 7T magnetic resonance (MR) images and their imaging features. Methods: A total of 33 healthy adults underwent 7T MR, and multiplanar images of 66 temporal lobes were reviewed independently by 2 neuroradiologists. The detectability of the HSR was calculated. In addition, the interobserver agreement on the rating scale was evaluated using the κ statistic. Results: Both observers identified HSRs with 7T MR images in all subjects. Excellent interobserver agreement was shown ( κ = 1.0). The shape of HSRs was variable (spot-like, curvilinear, ovoid, or beaded appearance). Volumes of the HSRs were not correlated with age. Conclusions: Hippocampal sulcus remnants are commonly seen in healthy nonelderly adults using 7T MR imaging. Accurate diagnosis of HSR based on the microanatomy of hippocampus makes it easier to differentiate them from lesions, and it may help prevent unnecessary treatment.